Risk assessment framework for cumulative effects (RAFCE) - Antwi, Effah Kwabena; Boakye-Danquah, John; Owusu-Banahene, Wiafe; Dabros, Anna; Eddy, Ian MS; Silver, Daniel Abraham; Abolina, Evisa; Eddy, Brian; Winder, Richard S. (Frontiers in Environmental Science, 2023)
Regional environmental risk assessment is a practical approach to understanding and proactively addressing the cumulative effects of resource development in areas of regional importance. However, regional assessment is methodologically complex, and frameworks to identify potential risks and prioritize regional issues to guide effective management decisions are lacking. This research develops a risk and impacts-based cumulative effects assessment framework for scoping regional cumulative effects issues and analyses and supports scenario planning to guide present and future regional assessment. We operationalized the framework to assess the risks and impacts of the proposed mining in the Ring of Fire region of Northern Ontario, Canada. We conducted a literature review to understand the key valued ecosystem components impacted by mining. Next, we organized an interdepartmental expert Bow-Tie Risk Assessment workshop and interviews to identify regional risks and impacts from mining. We developed an impact prioritization model that helped quantify and prioritize impacts associated with mining. The framework enabled us to identify: (a) the drivers and impacts of cumulative effects and potential preventive and mitigation measures for effective cumulative effect management, (b) major impact categories and components, as well as quantify and rank the impacts that are cross-cutting, multi-sector driven, synergistic and relevant to the region. Using the framework, we can visualize and understand the risk management process, identify policy and management issues, determine suitable interdepartmental collaboration to address cross-cutting issues, identify skills and capacity needed as well as areas of resource allocation for effective regional cumulative effects assessment outcomes. The framework is suitable for engaging diverse stakeholders, including scientists, industry, Indigenous communities, and resource managers in planning for regional cumulative effects assessment.